2015
DOI: 10.19030/jabr.v31i2.9121
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents Of Customer Loyalty In The Retailing Sector: The Impact Of Switching Costs

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Accordingly, our model introduces four value dimensions: product quality, service quality, shopping enjoyment, and self‐esteem. These values were chosen because they correspond to the main stream of experiential values reported in both Figure and Table : That is, the same dimensions as those found on the PERVAL scale in Sweeney and Soutar () were further replicated (e.g., Chi & Kilduff, ; Stan, ), and they are also the ones used in works on tourist shopping, such as the research by Guo et al () and Lloyd et al ().…”
Section: Empirical Study Developmentmentioning
confidence: 99%
“…Accordingly, our model introduces four value dimensions: product quality, service quality, shopping enjoyment, and self‐esteem. These values were chosen because they correspond to the main stream of experiential values reported in both Figure and Table : That is, the same dimensions as those found on the PERVAL scale in Sweeney and Soutar () were further replicated (e.g., Chi & Kilduff, ; Stan, ), and they are also the ones used in works on tourist shopping, such as the research by Guo et al () and Lloyd et al ().…”
Section: Empirical Study Developmentmentioning
confidence: 99%
“…quality of relationship with consumers, neatness of the store, product assortment). Previous studies have shown that store image is a predictor of satisfaction (Boloemer and de Ruyter 1998;Stan, 2014), of perceived value (Grewal et al 2004;Stan, 2014) and a predictor of loyalty (Bellenger et al 1976;Sirgy, 1985;Stan, 2014).…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Importance of trust on customers' loyalty was analysed by Wu et al (2015) and El-Manstrly (2016). Other authors (Stan, 2015;Ram & Wu, 2016) have evaluated the impact of perceived switching costs on loyalty. The commitment was included in some studies as well (Lariviere et al, 2014;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%